Cyanoprocariots and Water Weeds That Can Be Found in Soil - Abdullayeva Gulnoza Komiljonovna (Zien Journals, 2022)
The cellular structure of cyanoprocariots and algae growing in the soil environment and their adaptation to external environmental factors, morphological features and reproduction are described.
Keywords: blue-green algae; genome; colony; phytogeographic